KNOWLEDGE AND PEDAGOGICAL TECHNOLOGIES WITH DEVELOPMENT COMPETENCE IN THE TEACHING PROCESS - Izimbetova Roza Maqsetbaevna (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Аnnotation. This article provides information on the knowledge and pedagogical technologies with develop competence in the teaching process, the requirements for the professional skills of pedagogues, some trainings (technologies) and methods that can be used in the teaching process, the use of various pedagogical technologies and modern methods.